Análise da volatilidade dos preços futuros do açúcar - Sousa, Evemilia (2015)
This research aimed to analyze the dynamics and transmission of volatility of future sugar prices traded at the New York Stock Exchange for the Brazilian spot market between the years 2003 and 2014. The dynamics of volatility was estimated by the ARCH family models: GARCH, EGARCH and TARCH. In order to verify the transmission of the future foreign market prices to the Brazilian spot market ones, we applied Engler & Granger’s cointegration test. The results indicated: a) the existence of cointegration between the sugar prices of future foreign market and the Brazilian spot market prices, showing that future market price information is transmitted to the spot market prices in the three periods analyzed ; b) high volatility of the future sugar market, resulting from the sum of the volatility persistence coefficients; c) the presence of the asymmetric effect of volatility; d) absence of the leverage effect; e) in period 1 (05/20/2003 to 04/30/2014), the EGARCH model (2.1), presented the best fit to estimate the dynamics of the volatility of sugar future returns, considering the AIC and SBC criteria ; f) in period 2 (05/20/2003 to 06/21/2012), there was also the best fit through the EGARCH model (2.1); g) in period 3 (06/22/2012 to 04/30/2014), the GARCH model (1.1) presented the best fit in measuring the dynamics of the volatility of sugar future returns.